2022
DOI: 10.1021/acssynbio.2c00099
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Translation Systems Generate Genomically Engineered Escherichia coli Cells with Improved Growth Phenotypes

Abstract: Cellular translation is responsible for the synthesis of proteins, a highly diverse class of macromolecules that form the basis of biological function. In Escherichia coli, harnessing and engineering of the biomolecular components of translation, such as ribosomes, transfer RNAs (tRNAs), and aminoacyl-tRNA synthetases, has led to both biotechnology products and an expanded genetic code. However, the engineering potential of molecular translation is hampered by the limited capabilities for rapidly sampling the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…We anticipate our genome evolution platform playing an important role in screening efforts to improve strains for industrial and therapeutic applications. As an example, fitness‐conferring mutations that improve growth on diverse feedstocks (Mundhada et al , 2017 ; Gowland & Jewett, 2022 ) could be identified through the transposon‐mediated rewiring of GRNs. Similar mutations could then be rationally introduced without the transposon components to establish a final, stable strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipate our genome evolution platform playing an important role in screening efforts to improve strains for industrial and therapeutic applications. As an example, fitness‐conferring mutations that improve growth on diverse feedstocks (Mundhada et al , 2017 ; Gowland & Jewett, 2022 ) could be identified through the transposon‐mediated rewiring of GRNs. Similar mutations could then be rationally introduced without the transposon components to establish a final, stable strain.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge in directed genome evolution is our limited ability to dynamically track the mutations across a genome and mechanistically link these changes to the emergent phenotype (Luo et al , 2018 ). As a result, many of the processes generating genome‐wide structural heterogeneity in cells—for example, the duplication, translocation, transposition, or recombination of DNA segments (Kirchberger et al , 2020 )—have yet to be adapted into engineering approaches for fitness landscape exploration during laboratory evolution (Ma et al , 2019 ; Gowland & Jewett, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…C ell-like supramolecular assemblies, protocell models, and semisynthetic organisms can be employed for studying origins of cellular life, 1 membrane biogenesis and regulation, 2 cell development, 3 differentiation, 4 and signaling, 5 for producing biofuel, 6,7 or hormones 8 , for detecting metabolites, 9 pathogens, 10 or agricultural pollutants, 11 and for building cytomimetic tissues in regenerative medicine, 12 and targeted drug delivery. 13,14 A central goal in building cell-like materials is to configure the minimal requirements for cellular processes, which include, among others, sensing "extracellular" environment.…”
mentioning
confidence: 99%
“…Cell-like supramolecular assemblies, protocell models, and semisynthetic organisms can be employed for studying origins of cellular life, membrane biogenesis and regulation, cell development, differentiation, and signaling, for producing biofuel, , or hormones, for detecting metabolites, pathogens, or agricultural pollutants, and for building cytomimetic tissues in regenerative medicine, and targeted drug delivery. , …”
mentioning
confidence: 99%